Novel indicator film incorporating Dendrobium orchid extract and TiO2 nanoparticles for seafood freshness monitoring - Nattapong Kanha; Ratchadaporn Jaimun; Benjamard Rattanamato; Thunnop Laokuldilok (Future Foods)
This study aimed to develop a pH indicator film using a combination of hydrocolloids (polyvinyl alcohol, carboxymethyl cellulose, and rice flour; PCR film), Dendrobium orchid flower (DOF) extract, and TiO2 nanoparticles to monitor shrimp and crab freshness during 9 days of cold storage. LC-MS/MS analysis identified a rare anthocyanin, cyanidin-3-[6-sinapoyl-2-O-(2-(sinapoyl)glucosyl)-glucoside], in the DOF extract, responsible for its color expression. The DOF extract showed a clear color variation in different solutions (pH 1–13). TiO2 nanoparticles influenced the film's thickness, tensile strength (TS), elongation at break (EB), water vapor permeability (WVP), and color properties. Structural changes due to nanoparticles were confirmed via Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. PCR+DOF+8%TiO2 film showed the highest TS (13.75 ± 0.60 MPa), EB (2.24 ± 1.42 %), and WVP (3.57 ± 1.12 × 10-11 g·m·Pa-1·m-2·s-1) values and was more sensitive to ammonia vapor than acetic acid vapor. In practical applications, the film could effectively indicate shrimp spoilage through color change but was less precise for crab samples. The film effectively indicated shrimp spoilage through a color shift to green on the 4th day, correlating with total viable count and volatile nitrogen levels exceeding safe consumption thresholds. Thus, this film could serve as an efficient diagnostic tool for monitoring seafood spoilage.